KEBUDAYAAN DAN PERADABAN - Inrevolzon Inrevolzon (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2013)
Abstract:The word culture and civilization are two words that have enough understanding among the experts, this is due to their different points of view in accordance with the existing disciplines on them and see also the times. So for this time to approximately 160 cultural understanding definitions found. Besides, there are those who equate Culture with the understanding between civilizations and there is also a distinguishing sense. And there is also known a few words related to Culture and Civilization in words Civilization, Culture, hadara, Tsaqafah and civilization. Therefore, in this article will explain what the similarities and differences in these words. Keywords: culture, civilizations.